Cross-Border Cooperation in the Kaliningrad region: Problems and Prospects - Plyukhin Mikhail (Baltic Region, 2009)
Since the accession of Poland and Lithuania to the EU, the nature, forms and content of their border cooperation with the Kaliningrad region have fundamentally changed. There is a tendency towards strengthening the neighborhood policy. The already gained extensive and varied experience of the participation of the Kaliningrad region in the IN-TERREG Programme contributed to the socio-economic development of the region. The new financial tools should be linked to the regional development strategies of the neighboring territories. Efficient use of both Russian and the EU funds will help develop a new technology for regional development of North-West Russia.